2013
DOI: 10.1111/hepr.12116
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and its implication in the side‐effects of interferon‐based treatment of patients with chronic viral hepatitis: Pharmacological interventions

Abstract: Depression is a frequent side-effect of interferon-based treatment of patients with chronic viral hepatitis, that may lead to reduction or discontinuation of treatment. Clinical trials data showed the importance of therapy of psychiatric disorders for a successful antiviral treatment. Emerging evidence suggests that interferon may cause depression affecting serotonin synthesis via increased activity of indoleamine 2,3-dioxygenase. Serotonin reuptake inhibitors significantly improve mood disorders, but the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In recent studies, it was found that patients with mild HCV-infection during magnetic resonance spectroscopy have a pronounced dysfunction of choline and creatinine metabolism in the basal ganglia and white matter of the brain compared with patients without a history of hepatitis. In comparison with the process observed in hepatic encephalopathy, higher concentrations of cerebral choline were recorded in patients in this study, which ultimately serves as evidence of the effect on cognitive functions (Stasi et al, 2014).…”
Section: )supporting
confidence: 57%
See 2 more Smart Citations
“…In recent studies, it was found that patients with mild HCV-infection during magnetic resonance spectroscopy have a pronounced dysfunction of choline and creatinine metabolism in the basal ganglia and white matter of the brain compared with patients without a history of hepatitis. In comparison with the process observed in hepatic encephalopathy, higher concentrations of cerebral choline were recorded in patients in this study, which ultimately serves as evidence of the effect on cognitive functions (Stasi et al, 2014).…”
Section: )supporting
confidence: 57%
“…2, p. 94-107 course of the disease suggests a possible role of chronic viral hepatitis viruses in inducing dysfunction of selective aminergic systems (Weissenborn et al, 2006). On the other hand, patients undergoing interferon therapy the appearance of depression correlates with the depletion of serotonin in platelets, possibly due to the effectiveness of antidepressants that inhibit serotonin reuptake (Stasi et al, 2014). There are other putative mechanisms of cognitive deficits associated with cytokines released during systemic or immune activation of the brain (Stasi et al, 2014).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic innervation to the gut is supplied by neurons of the ENS, including the myenteric and submucosal plexus. Extrinsic innervation is provided by the autonomic nervous system (both sympathetic and parasympathetic) and is arranged to function in a bidirectional manner [ 11 , 40 , 41 ]. Moreover, the 5-HT concentrations are regulated by its reuptake, which is operated by the 5-HT transporter (SERT) expressed both in neurons and intestinal epithelium [ 40 43 ].…”
Section: Discussionmentioning
confidence: 99%